Efforts to Improve the Performance of Posyandu Cadres Based on Analysis of Cadre Empowerment in Tulungagung Regency, Indonesia (Medico Legal Update, 2020)
Posyandu is one form of Community-Based Health Efforts held together with the community in obtainingbasic health services. The cadre’s role is to provide health information to the community, as a communitymobilizer to come to Posyandu and a motivator to realize maternal and child health. The research was aimedat developing an effort to improve the performance of Posyandu cadres based on an analysis of empowermentin Tulungagung Regency. The study was conducted using observational analytic method with a sampleof 32 Posyandu. The study was conducted in Tulungagung Regency in January-March 2020. The resultsshowed that there was a relationship between the process of empowering and capability empowermentwith the performance of Posyandu cadres (0.019; 0.001). There was a relationship between cadre trainingand alignment (0.002); the relationship between the availability of facilities and the role of the village withcapability (0.042; 0.028) and the relationship between the development of cadres and trusts (0.028). Itcould be concluded that the performance of Posyandu cadres was influenced by the process of empoweringalignment and capability. While trust was not related to the performance of Posyandu cadres. The processof empowering alignment was influenced by cadre training; capability was influenced by the availability offacilities and the role of villages.